Place of Work and Place of Residence: Informal Hiring Networks and Labor Market Outcomes - Bayer, Patrick; Ross, Stephen L.; Topa, Giorgio (Journal of Political Economy, 2008)
We use a novel research design to empirically detect the effect of social interactions on labor market outcomes. Using Census data on residential and employment locations, we examine whether individuals residing in the same city block are more likely to work together than those in nearby blocks. We find evidence of significant social interactions. The estimated referral effect is stronger when individuals are similar in sociodemographic characteristics. These findings are robust across specifications intended to address sorting and reverse causation. Further, the increased availability of neighborhood referrals has a significant impact on a wide range of labor market outcomes. (c) 2008 by The University of Chicago. All rights reserved.